Infectious disease, shifting climates, and opportunistic predators: cumulative factors potentially impacting wild salmon declines. (27th May 2014) - Miller, Kristina M.; Teffer, Amy; Tucker, Strahan; Li, Shaorong; Schulze, Angela D.; Trudel, Marc; Juanes, Francis; Tabata, Amy; Kaukinen, Karia H.; Ginther, Norma G.; Ming, Tobi J.; Cooke, Steven J.; et al.
Abstract Emerging diseases are impacting animals under high‐density culture, yet few studies assess their importance to wild populations. Microparasites selected for enhanced virulence in culture settings should be less successful maintaining infectivity in wild populations, as once the host dies, there are limited opportunities to infect new individuals. Instead, moderately virulent microparasites persisting for long periods across multiple environments are of greatest concern. Evolved resistance to endemic microparasites may reduce susceptibilities, but as barriers to microparasite distributions are weakened, and environments become more stressful, unexposed populations may be impacted and pathogenicity enhanced. We provide an overview of the evolutionary and ecological impacts of infectious diseases in wild salmon and suggest ways in which modern technologies can elucidate the microparasites of greatest potential import. We present four case studies that resolve microparasite impacts on adult salmon migration success, impact of river warming on microparasite replication, and infection status on susceptibility to predation. Future health of wild salmon must be considered in a holistic context that includes the cumulative or synergistic impacts of multiple stressors. These approaches will identify populations at greatest risk, critically needed to manage and potentially ameliorate the shifts in current or future trajectories of wild populations.